Program for Developing Reading Comprehension Skills in the Fourth Grade Students with Primary Dyslexia at Harvard High School of Guayaquil. - Terán García, Enrique Rainiero (2016)
This project aims to test the effectiveness of an individualized educational EFL program addressed specifically to students with primary dyslexia who are from the first baccalaureate. Also, it intends to discover efficient teaching methods and techniques that will help students with primary dyslexia to develop their capacity in the area of reading comprehension in EFL classrooms. There were several resources researched to create the theoretical framework and the Literature review of this work. It was reviewed books about learning disabilities, research papers form scholars and web pages with very important documents to be used specially for dyslexia, and other specific learning disabilities. This was used to clarify and define learning disabilities problems and their effects on students. It was noticed that three students from Harvard School had problems while using reading and writing skills. It was compiled composition samples and reading comprehension exercises for gathering data to know the level of performance. Upon this information it was constructed statistical analysis and the final conclusions that led to the proposal. The educational proposal is presented as an Individualized Educational Program which is important for teachers, students and the educational institution in order to work in a real inclusive system. For understanding how the IEP works and how it can be modified for those students who have a learning disability it was researched from two different materials, and adapted to be used for the local context.